Changes in Volatile Compound Composition in Satsuma Mandarin Pulp during Different Ripening and Storage Periods - Wenyi YAN; Yating XIE; Yingke MA; Yan YANG; Ainong YU (Shipin gongye ke-ji)
This study provided theoretical support for the quality evaluation, harvesting and storage of Satsuma mandarin. This study characterized volatile compounds in three cultivars (Kamei, Nichinan, Okitsu) and tracked compositional changes in the composition of volatile compounds in Kamei Satsuma mandarin pulp during the pre-ripening, ripening and over-ripening stages, as well as during the storage period under ambient conditions (temperature: 22.84±1.45 ℃, humidity: 61.6%±3.38%), using the HS-SPME-GC-MS method. The results showed that a total of 16 volatile compounds were detected in the pulp of different Satsuma mandarins, of which 13 were terpenoids. Analysis of the volatile compound content of Kamei Satsuma mandarin pulp over different ripening and storage periods revealed that volatile content was higher during pre-ripening than during ripening and over-ripening stages with D-limonene being the most prominent at 899.96 μg/L. The volatile compound content in the pulp of Kamei Satsuma mandarin first increased and then decreased during storage. Analysis of the content of each volatile substance in the three mature varieties revealed that most of the compounds were higher in Kamei, γ-terpinene and carvacrol content was higher in Nichinan, at 1.11 μg/L and 1.66 μg/L. And nerol was higher in Okitus, at 1.95 μg/L. Analysis of the odor activity values of the volatile compounds indicated a floral, fruity, and sweet odor for Satsuma mandarin, with D-limonene, β-damascenone, and linalool contributing the maximum to the aroma.